Comparative analysis of the AE signals generated by partial single- and multi-source discharges - Cichoń, Andrzej; Boczar, Tomasz; Borucki, Sebastian; Lorenc, Marcin (Archives of Acoustics, 2007)
Within the research work carried out, the results of which are presented in this paper, acomparative analysis of the acoustic emission (AE) signals generated by partial single- andmulti-source discharges (PDs) was carried out. The investigations were carried out in a modelsystem, in which PDs were generated with two identical spark-gaps. In the work, spark-gapsin the surface system were used, due to the fact that this is the PD form occurring most oftenin power transformers. The AE signals were registered with a contact transducer placed on theexternal part of the tub. For the AE signals generated by both single-source PDs and multisourcePDs, a frequency analysis using a fast Fourier transform (FFT) and an analysis in thetime-frequency domain using a short-time Fourier transform (STFT) were carried out. Theresults of the frequency analysis are presented in the form of power density spectra, and thetime-frequency analysis results in the form of spectrograms. Analyzing the research results thesignals registered were compared from the point of view of identification possibilities of theparticular PD forms. The aim of the research work carried out is also proving the usefulnessof the AE method for diagnosing the condition of high-voltage power appliance insulation, inwhich multi-source discharges occur.